Inflammatory Cytokine Profiles of Semen Influence Cytokine Responses of Cervicovaginal Epithelial Cells - Rametse, Cosnet L.; Adefuye, Anthonio O.; Olivier, Abraham J.; Curry, Lyle; Gamieldien, Hoyam; Burgers, Wendy A.; Lewis, David A.; Williamson, Anna-Lise; Katz, Arieh A.; Passmore, Jo-Ann S. (Frontiers in Immunology, 2018)
Genital inflammatory cytokine responses increase HIV risk. Since male partner semen is a complex mixture of immune-modulatory prostaglandins and cytokines, we hypothesized that exposure to semen may influence genital inflammation in women. Here, we investigated cytokine response kinetics of ectocervical cells following stimulation with seminal plasma from HIV-negative and HIV-positive men characterized as having low or high concentrations of inflammatory cytokines. Irrespective of the HIV status or semen cytokine profile, in vitro stimulation of ectocervical cells with seminal plasma resulted in significantly elevated concentrations of secreted IL-6, IL-8, TNF-β, MCP-1, GM-CSF, and VEGF within 8 hours of stimulation, which tended to decline by 24 hours, although this was only significant for TNF-β. Consistent with this, cervical cells responded to seminal plasma with increases in IL-8 and IL-1β mRNA expression of 10-fold. These findings suggest that the impact of semen on local female genital cytokines is likely transient. Although these findings suggest that the impact of semen on local female genital cytokines may not be sustained long-term, this heightened genital inflammation may have implications for HIV risk in women.